Rotational Force Mitigation Systems in Cycling Helmets: A Narrative Review of the Effectiveness of MIPS, WaveCel and SPIN in Preventing Traumatic Brain Injuries - Urban, Jan; Noskowicz, Jan; Próchnicka, Magdalena; Nowak, Dominika; Zarzycki, Adam; Siwek, Michał; Hamouta, Jakub; Długosz, Patrycja; Konat, Julia; Doroszuk, Wiktor (Quality in Sport, 2025)
Background: Head injuries remain a prevalent and serious concern in cycling, often resulting in traumatic brain injuries (TBIs) such as concussions and diffuse axonal injuries. Traditional helmets primarily reduce linear forces but are less effective against rotational acceleration, a key factor in TBIs. Objective: This review aims to evaluate the effectiveness of three rotational force mitigation technologies—MIPS (Multi-directional Impact Protection System), WaveCel, and SPIN (Shearing Pad INside)—in preventing TBIs in cyclists. Methods: A literature review was conducted using databases including PubMed and Google Scholar. Search terms included: "head injury", "helmet", "MIPS", "WaveCel", "SPIN", and "concussion prevention". Only peer-reviewed studies published from 2015 onward were included to ensure relevance and up-to-date findings. Key Results: The three systems vary in design and biomechanical performance. MIPS shows consistent reduction in rotational acceleration across various impact conditions. WaveCel demonstrates strong energy absorption capabilities and protection in angled impacts, while SPIN shows promising results in reducing strain on brain tissue. However, direct comparative clinical outcome data remain limited. Conclusions: While all three systems improve protection against rotational forces, current evidence suggests that MIPS and WaveCel offer the greatest potential for reducing TBIs. Further real-world injury data and standardized testing protocols are needed to better assess long-term effectiveness and guide helmet design improvements.